2001
DOI: 10.2134/agronj2001.93149x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Biomass and Phenolic Production in Grain Sorghum Grown under Different Conditions

Abstract: The total phenol pool (kg ha−1) of the aerial parts and roots of sorghum (Sorghum bicolor L. cv. CE145−66) crops and their relationships to dry matter and total phenol concentrations (g kg−1) were studied in four different data sets (2 sites × 2 yr for a total of 52 smallholder fields) in Senegal. The total phenol pool size varied from 4 to 156 kg ha−1 in the aerial parts and from 1 to 16 kg ha−1 in the roots. The phenol pool size was closely correlated with the amount of dry matter in both the aerial parts (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 34 publications
(38 reference statements)
0
10
1
Order By: Relevance
“…The trend that we observed of an increase in the plant performance trait of dried plant biomass to be associated with increased phenolic concentrations is not in line with the dilution effect theory of chemical ecology that states that when growth conditions are favorable, less secondary chemicals will be produced as a resource trade off (Nurmi et al 1996;Riipi et al 2002). However, several other studies have found similar trends as in our study regarding the ability of plants to support both growth and defense (Briggs and Schultz 1990;Riipi et al 2002;Sene, Dore, and Gallet 2001). Additionally, our results are not in line with the optimal defense theory of chemical ecology…”
contrasting
confidence: 66%
“…The trend that we observed of an increase in the plant performance trait of dried plant biomass to be associated with increased phenolic concentrations is not in line with the dilution effect theory of chemical ecology that states that when growth conditions are favorable, less secondary chemicals will be produced as a resource trade off (Nurmi et al 1996;Riipi et al 2002). However, several other studies have found similar trends as in our study regarding the ability of plants to support both growth and defense (Briggs and Schultz 1990;Riipi et al 2002;Sene, Dore, and Gallet 2001). Additionally, our results are not in line with the optimal defense theory of chemical ecology…”
contrasting
confidence: 66%
“…Phytotoxic compounds in sorghum stalks and leaves, such as phenolics or cyanogenic glucosides, may have contributed to this allelopathic effect (Halkier and Møller 1989;Sène et al 2001). In the present study, growth chamber assays were used to determine whether cycling of sorghum seedlings or cycling of wheat in soil previously cropped with sorghum genotypes would effect seedling growth.…”
Section: Discussionmentioning
confidence: 98%
“…The con cen tra tions of phenolics might have depended on the weather course. It is known that accu mu la tion of phenolics in plants are strongly as soci ated with the crop en vi ron ment (Guinn and Eindenbock 1982, Duke 1985, Hor ner 1990, SPne et al 2001. En vi ron men tal fac tors, in clud ing light and wa ter def i cit, in flu ence the syn the sis and conse quently the con cen tra tion of phenolics in the plant tis sue and in most cases en hance allelo chemicals pro duc tion.…”
Section: Phenolicsmentioning
confidence: 99%
“…Allelopathically ac tive compounds from plants act as nat u ral her bi cides and some have been ex plored as nat u ral sub sti tutes for com mer cial her bi cides (Duke et al 2000). The selec tion of ge no types with the en hanced allelochemical po ten tial, fo cused on the weed growth con trol ling prop er ties and in creas ing grain yields, has been car ried out in sev eral field crops (Putnam et al 1983, Rice 1984, Yenish et al 1996, SPne et al 2001. Some allelochemicals iso lated from higher plants in hibit pho to syn the sis and con se quently the pro duc tion and growth of com pet ing plants in clud ing weeds (Einhellig et al 1993, Gon za lez et al 1997, Smith and Doan 1999, Wu et al 1999.…”
Section: Introductionmentioning
confidence: 99%